Antilung cancer effect of ergosterol and cisplatin-loaded liposomes modified with cyclic arginine-glycine-aspartic acid and octa-arginine peptides. Issue 33 (August 2018) - Wu, Meijia; Huang, Ting; Wang, Juan; Chen, Ping; Mi, Wanwan; Ying, Yuanyuan; Wang, Hangli; Zhao, Dandan; Huang, Shengwu
Abstract: Background: Lung cancer is one of the most important diseases threatening human health, and targeted therapy has become the main research direction. This work, therefore, aimed to develop cyclic arginine-glycine-aspartic (RGD) and octa-arginine (R8) peptide-modified ergosterol (ERG)-combined cisplatin (diamminedichloridoplatinum(II) [DDP]) liposomes (LIP) as a drug delivery system. Methods: Soybean phospholipids (SPC) and cholesterol (Chol) were selected to prepare different LIPs: ERG-loaded LIP (ERG-LIP), DDP and ERG-LIP (DDP/ERG-LIP), R8 peptide-modified DDP and ERG-LIP (R8-DDP/ERG-LIP), and cyclic RGD and R8-DDP/ERG-LIP (RGD/R8-DDP/ERG-LIP). The quality, tumor sphere penetrating ability, in vitro cellular uptake, mechanism of cellular uptake, and in vitro cytotoxicity of RGD/R8-DDP/ERG-LIP were evaluated. Results: The LIP quality evaluation revealed that RGD/R8-DDP/ERG-LIP is round with a double-layer structure. The average particle size, dispersion coefficient of the polydispersity index (PDI), and zeta potential of RGD/R8-DDP/ERG-LIP were 155.2 ± 8.7 nm, 0.102, and 4.74 ± 0.7 mV, respectively. Furthermore, the LIPs were stable in the serum, and obviously inhibited the growth of A549 lung cancer cells with RGD/R8-DDP/ERG-LIP exhibiting the strongest inhibitory effect. The highest cellular uptake rate, which was at 4 hours, was exhibited by RGD/R8-DDP/ERG-LIP in a concentration-dependent manner. Conclusion: The results showed that LIP uptake by A549 cells was mainly by the clathrin-mediated endocytosis pathway (chlorpromazine). The results also suggest that RGD/R8-DDP/ERG-LIP might be a promising drug delivery system to improve antilung cancer drug effect and tumor-targeting in vitro. Abstract : Supplemental Digital Content is available in the text